ATRAKSI WISATA MENUMBAI DI TAMAN NASIONAL TESSO NILO DESA LUBUK KEMBANG BUNGA KECAMATAN UKUI KABUPATEN PELALAWAN - Widyaningsih, Desi; ", Yoserizal (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
The purposed of this research to know what factors supporting by menumbai tradition to be a tourist attraction in Tesso Nilo National Park and the regency to know any tourist activity that can be done by tourists in menumbai tradition. This research used descriptive qualitative method for analyzed the problem. The research subjects are 10 people by using purposive sampling. And then the technique for collected the data in this research are using observation, interview and documentation. Based on the research the factors supporting menumbai tradition to be a tourist attraction in the park Tesso Nilo in Lubuk Kembang bunga is accessibility, harvesting time, safety and comfort of visitors. Attraction are obtained by visitor is natural attraction, and cultural attraction. In terms of accessibility to the Tesso Nilo National Park is accessible, in terms of execution time menumbai traditions can not any time, cause honey have internal in harvest time, as well as attractions menumbai very safe and convenient for travelers. And tourist activity in menumbai attraction, visitors can also enjoy the travel additional, like fringe of the river, fishing, see the making equipment traditional, ritual procession menumbai and processing “Madu Sialang”. The results of this study tour menumbai very appropriate to be used as a tourist attraction in the Tesso Nilo National Park in the Lubuk Kembang Bunga Village. Keywords: Menumbai Attractions, accessibility, harvesting time, security and comfort, natural attractions, cultural attractions.